2000
DOI: 10.1074/jbc.c000464200
|View full text |Cite
|
Sign up to set email alerts
|

Excitation-Contraction Coupling Is Not Affected by Scrambled Sequence in Residues 681–690 of the Dihydropyridine Receptor II-III Loop

Abstract: A peptide corresponding to residues 681-690 of the II-III loop of the skeletal muscle dihydropyridine receptor ␣ 1 subunit (DHPR, ␣ 1S ) has been reported to activate the skeletal muscle ryanodine receptor (RyR1) in vitro. Within this region of ␣ 1S , a cluster of basic residues, Arg 681 -Lys 685 , was previously reported to be indispensable for the activation of RyR1 in microsomal preparations and lipid bilayers. We have used an intact ␣ 1S subunit with scrambled sequence in this region of the II-III loop (␣ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
41
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 16 publications
7
41
0
Order By: Relevance
“…These studies have identified a different region (amino acid residues 720 -765) to be the critical site for DHPR and RyR interaction in skeletal muscle (9). Also, skeletal type EC coupling was unaffected when an ␣ 1s -DHPR with a scrambled sequence corresponding to pA (residues 681-690) was expressed by dysgenic myotubes (16). Since both active and inhibitory effects of peptide A on RyR channels have been reported, the mechanism of the interaction of peptide A with RyR1 must be complex (12,15).…”
Section: Scorpion Peptide-induced Proportional Gating Of Ryr1mentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have identified a different region (amino acid residues 720 -765) to be the critical site for DHPR and RyR interaction in skeletal muscle (9). Also, skeletal type EC coupling was unaffected when an ␣ 1s -DHPR with a scrambled sequence corresponding to pA (residues 681-690) was expressed by dysgenic myotubes (16). Since both active and inhibitory effects of peptide A on RyR channels have been reported, the mechanism of the interaction of peptide A with RyR1 must be complex (12,15).…”
Section: Scorpion Peptide-induced Proportional Gating Of Ryr1mentioning
confidence: 99%
“…These actions of pA were also found to extend to RyR2, suggesting a modulatory influence downstream of the skeletal ␣ 1s -DHPR/RyR1 interaction (12). However, expression of ␣ 1s -DHPR chimeras in dysgenic myotubes has shown that the pA region of the II-III loop was not essential for engaging skeletal type EC coupling (16), whereas a 46-amino acid fragment (Leu 720 -Gln 765 ) was essential for bidirectional signaling (9,(17)(18)(19). Although the action of pA and related peptides may not be directly involved in mediating bidirectional signaling in skeletal EC coupling, they are very useful in defining basic properties of RyR gating.…”
mentioning
confidence: 98%
“…A strict alignment (Block et al, 1988) allows physical coupling between the II-III loop of the DHPR and the RyR to initiate skeletal-type excitation-contraction (EC) coupling (which is independent of external Ca 2 þ ). Although the A region of the II-III loop is not required for EC coupling (Proenza et al, 2000;Wilkens et al, 2001), it has been implicated in the overall physical interaction between the DHPR and RyR (Ahern et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, most of our previous studies were carried out at [Ca 2ϩ ]s higher than 0.2 M; many experiments were carried out at or higher than 1.0 M. Because the in vivo studies of E-C coupling described in the Introduction (3,4,16) Concentration Ranges in an RyR1-specific Manner- Fig. 1, A and B shows the effects of 50 M peptide A (a maximally activating concentration) on the ryanodine binding activity of the RyR of skeletal muscle and cardiac muscle microsome preparations, respectively, at different Ca 2ϩ concentrations in the assay solution.…”
Section: Resultsmentioning
confidence: 99%
“…However, according to the recent report of Proenza et al (16), scrambling of the amino acid sequence in the peptide A-10 region, which produced a severe loss of the activating function of peptide A-10 in our in vitro experiments (11), produced no detectable changes in E-C coupling in the dysgenic myotubes. Similarly, chimeric construct, in which the Leu 720 -Leu 764 region is the skeletal muscle-type sequence, but the rest is identical to the housefly II-III loop with the sequence quite dissimilar to the skeletal muscle sequence, produced essentially the same E-C coupling activity as the wild-type skeletal muscle system (17).…”
mentioning
confidence: 89%